PENGARUH JERAMI PADI DAN RASIO PUPUK UREA, TSP, KCl TERHADAP PERTUMBUHAN DAN PRODUKSI KEDELAI ( Glycine max (L) Merril. ) - Jamili, M Joehari; Sjofjan, Jurnawaty; Amri, Al Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research was conducted to find out the effect of rice straw and ratio of Urea, TSP, KCL on the growth and production of soybean. This research has been conducted in the experimental farm, Faculty of Agriculture University of Riau, from January to April 2016. This study used randomized block design (RAK), arrange in a factorial with 2 factors, factors of rice straw mulch with 3 levels doses of 0 kg/Ha, 5 kg/Ha, 10 kg/Ha and factor ratio of Urea, TSP, KCL with 4 levels doses of 0 kg/Ha, 25, 50, 50 kg/Ha, 50, 100, 100 kg/Ha, 75, 150, 150 kg/Ha, two factors combined to obtain 12 combined treatment, for each treatment consisted of three replications, in order to get 36 experimental units. The data were analyzed by analysis of variance and significantly different continued with Duncan New Multiple Range Test (DNMRT) at 5% level. Each experimental unit consisted of 52 plants, only seven plants become sample. The parameters measured were the number of the effectiveness root nodules per plant, the growth rate of plants, weeds, number of pods per plant, pods percentage pithy, dry seed weight/m2, and the weight of 100 seeds. Research data show that rice straw dose of 10 ton/Ha and ratio of Urea, TSP, KCl doses of 50, 100, 100 kg/Ha produces a dry seed weight of 2,69 tons/Ha, higher than without treatments is 1,3 tons/Ha. Keywords: soybeans, organic mulch, rice straw.